Relações entre atributos, benefícios e valores na decisão de compra de gasolina aditivada - Mesquita, Marcelo Andrade Botelho (2007)
The present dissertation had as its major objective to investigate the purchase behavior of midgrade gasoline consumers in the perspective of Means-End Chain theory. The sample was composed of 55 midgrade gasoline consumers in the city of Montes Claros/MG, Brazil. Accordingly to the Means-End Chain theory, it is possible to understand the consumers’ decision process and purchase behavior by analyzing their value network. Consumers seek for products attributes that they believe will bring benefits. However, the importance of those benefits is settled by the consumers’ personal values. The deep interview technique of Laddering was used to access consumers’ cognitive structures. Through that, it was possible to identify 5 attributes, 22 benefits and 13 personal values. The inter-relations among those elements were represented in a Hierarchical Value Map (HVM). From the HVM, eight different groups of midgrade gasoline consumers were identified: those who are future aware, those who care for money to be happy and live well, those who care for traffic safety, those who care for no stress, those who care for keeping one’s word, those who are pleased and proud of their vehicle, the accomplishers and those who are ecologically aware. The analysis of motivations behind the mentioned personal values revealed that a relevant part of the option for midgrade gasoline is related to the search for stability and conservation, which suggests the existence of a market nixie that can be explored by the fuel companies. From those and other findings, managerial implications and suggestions for future studies were presented.